Comparative Study on the Proximate Composition and Amino Acid Levels in Chanterelle (Cantharellus cibarius) and Wood Ear (Auricularia auricula) Mushroom Samples - Adebisi, Arowora Kayode; Abah, Moses Adondua; Ugwuoke, Kenneth Chinekwu; Dooshima, Arowora Mercy; Ndoma, Odi Raphael; Okani, Precious Chizaram; Ominisan, Kimi Smith; Gbadebo, Adetoyi Moses; Olamilekan, Aliyu Najeeb; Kwame, Asare Bernard (Darul Yasin Al Sys, 2024)
Mushrooms have been consumed by mankind for millennia. They are macrofungi with a distinctive fruiting body which can be hypogeous or epigeous, large enough to be seen with unaided eyes. They are not widely consumed due to lack of information on its nutritive value. Therefore, this research was carried out to compare the proximate gross energy composition as well as amino acids levels in two selected edible mushrooms (Cantharellus cibarius and Auricularia auricula). Fully matured species of Chanterelle mushroom (Cantherellus cibarius) and Wood ear mushroom (Auricularia auricula) were collected from different parts of Southern and Northern Cross River; Ikom and Bekwara precisely. The collected samples were air dried for 5 days and then stored in transparent polythene bag for analysis. The dried and stored mushroom were pounded to powdered form and then subjected to amino acid analysis using isocratic HPLC and proximate analysis for proximate composition using the standard methods of Association of Official Analytical Chemist (AOAC). The results of this research showed that chanterelle mushroom has high concentration of amino acids compared to Wood ear mushroom. However, there was significant differences (p<0.05) in the levels of isoleucine in both mushrooms. There were no significant differences in the proximate composition and gross energy levels of both mushroom species. Some of the amino acids detected in both mushrooms were: methionine, threonine, isoleucine, leucine, phenylalanine, valine, tryptophan, histidine, arginine, aspartic acid, glycine, alanine and glutamic acid. Based on the findings of this study, the two edible mushrooms were observed to have appreciable levels of gross energy and amino acids. However, Chanterelle mushroom had higher protein composition than wood ear. Hence, it can be concluded that Chanterelle mushroom has greater nutritive value and more suitable for consumption.